Environmental movements in a material world. A relational perspective on single-use plastic in Penzance, UK - Idies, Yusif; Mössner, Samuel (Frontiers in Sustainable Cities, 2023)
While environmental movements usually address climate change and sustainability in a broader sense, there are specific and sometimes very concrete issues and themes that are more prominently discussed than others. In the discursive battle about the big and important ideas, some are considered more important than others or simply better and stronger to mobilize society: acid rain in the 1980s, the ozone hole in the 1990s, the melting of pole-ice during the 2000s, and finally and more recently, plastic islands in our oceans. With this article we aim at contributing to a more detailed understanding of how specific issues of sustainability are brought forth. While the notion of frame allows for investigating immaterial discourses, narratives and values as a result of deliberate framing choices by social-movement leaders, we contend that specific issues – in this case: single-use plastics – could be characterized as rather emergent and that their material properties also play a key role for their functioning as a least common denominator. By following the concept of “boundary objects” we want to extend the range of social movement approaches in order to understand how the process of framing is put into work practically and materially.